Reframing Collaborative Governance for Local Economic Empowerment: Institutional Insights from Traditional Culinary MSMEs - Ermanovida Ermanovida; Tuty Khairunnisyah; Aulia Utami Putri; Norma Juainah (MASI Mandiri Edukasi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening local economies and preserving cultural identity. In Kabupaten Ogan Ilir, traditional culinary MSMEs hold significant potential as drivers of regional economic development; however, their management remains constrained by fragmented coordination, limited institutional capacity, and suboptimal stakeholder collaboration. This study aims to analyze the implementation of collaborative governance in managing traditional culinary MSMEs in Ogan Ilir Regency. A qualitative descriptive approach was employed to examine the implementation of collaborative governance. The study is guided by the model proposed by Chris Ansell and Alison Gash, focusing on five analytical components: direct stakeholder dialogue, trust development, commitment to collaborative processes, shared understanding, and intermediate outcomes. Data were gathered through in-depth interviews, observational fieldwork, and document review, incorporating insights from local government institutions and associated actors, MSME actors, community groups, and supporting institutions. The findings indicate that collaborative governance practices have begun to develop but remain partially institutionalized. Dialogue mechanisms exist yet are not conducted routinely; trust among actors has improved at the institutional level but remains fragile operationally; and commitment is stronger within government institutions than among non-state actors. While intermediate outcomes such as increased business licensing, improved packaging, and digital marketing adoption have been observed, collaboration is still predominantly top-down and lacks sustained multi-actor engagement. Strengthening structured coordination forums, clarifying stakeholder roles, and enhancing participatory mechanisms are essential to achieving a more integrated and sustainable collaborative governance model for culinary MSME development.